2019
DOI: 10.3389/fnmol.2019.00228
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Compensatory Increase in Shank3 Transcripts in Shank3 Knock-Out Mice Having Partial Deletions of Exons

Abstract: Genetic variants of the SH3 and multiple ankyrin repeat domains 3 (SHANK3) gene, which encodes excitatory postsynaptic core scaffolds cause numerous brain disorders. Several lines of Shank3 knock-out (KO) mice with deletions of different Shank3 exons have previously been generated and characterized. The different Shank3 KO mouse lines have both common and line-specific phenotypes. Shank3 isoform diversity is considered a mechanism underlying phenotypic heterogeneity, and compensatory changes through regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 32 publications
4
17
0
Order By: Relevance
“…In contrast to our previous in vitro results, we did not observe any significant difference in morphological parameters of dendrites and spines from transplanted CTR and ASD neurons. Since SHANK3 is known to play a crucial role in both synaptic development and function, our results suggest that compensatory changes may occur under in vivo conditions, as was recently observed in Shank3 knock-out mice having partial deletions of exons 32 . Other authors also reported unexpected levels of complexity and modularity of SHANK3 functions in vivo using mouse models 33 .…”
Section: Discussionsupporting
confidence: 75%
“…In contrast to our previous in vitro results, we did not observe any significant difference in morphological parameters of dendrites and spines from transplanted CTR and ASD neurons. Since SHANK3 is known to play a crucial role in both synaptic development and function, our results suggest that compensatory changes may occur under in vivo conditions, as was recently observed in Shank3 knock-out mice having partial deletions of exons 32 . Other authors also reported unexpected levels of complexity and modularity of SHANK3 functions in vivo using mouse models 33 .…”
Section: Discussionsupporting
confidence: 75%
“…One might argue that mRNAs coding for truncated mutant forms of Shank3, as observed in our patient, will be degraded by the mechanism of nonsense‐mediated decay (NMD), to the effect that the truncated protein will not be produced. However, analysis of Shank3 transcripts in two mouse lines with truncating deletions in exons 13‐16 (central part of the protein, (Jin et al, 2019)) or exon 21 (C‐terminal part; (Qin et al, 2018)) demonstrated a strongly increased expression of transcripts coding for the remaining N‐terminal part of the protein. Thus, the lack of post‐synaptic Shank3 leads to a compensatory activation of upstream Shank3 promoters.…”
Section: Discussionmentioning
confidence: 99%
“…The results were analyzed using the comparative Ct method and were normalized against the levels of housekeeping gene Gapdh ( Han et al, 2013a ). The primer sequences for real-time PCR were described previously ( Jin et al, 2019a ) or are as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Shank3B KO mice ( Peca et al, 2011 ) in which exons 13–16 of the Shank3 gene are replaced with the Neo cassette are among the most extensively characterized ASD models. We recently identified an unexpected increase in the mRNA expression of Shank3 exons 1–12 (i.e., 5′ of the Neo cassette) in the brains of Shank3B KO mice ( Jin et al, 2019a ; Lee et al, 2019a ). In particular, the mRNA levels of Shank3 exons 1–12 increased significantly in the cortex, striatum, and hippocampus of both juvenile and adult Shank3B KO mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation